Evaluation of Continuous Educational Programs as Viewed by the Employees of the Great Naft Hospital - Jeyran Ostovarfar; Maral Ostovarfar; Somayeh Zare; Leila Moradi; Elham Makiabadi; Abdolrahim Asadollahi (Shiraz University of Medical Sciences, 2018)
Background: Continuous educational programs are one of the essential ways to promote human resources; inconsistency of the courses with individual and organizational needs may lead to organizational dissatisfaction, job performance reduction, and time and capital waste. The study aimed to evaluate the attitudes of the employees about in-service continuous educational programs; they participated in the above-mentioned programs in the continuous educational units from 2006 to 2017 in Ahwaz city, Iran. Methods: In this cross-sectional study, all the treatment and administrative employees in the hospital participated in the educational plans. Out of 548 employees, 225 were selected using the ratio-random sampling method in the late 2017. The study instrument was a validated questionnaire with 66 items and 5 scales of adaptation, efficient management, individual development, growth of attitudes, employees' knowledge and skills, and managers' support for implementing operational programs; its validity was measured using Cronbach's Alpha (α=0.93). The collected data were analysed in SPSS V.23 using descriptive statistics, mean scores, SD, χ2 test, ANOVA, and t-test. Results: Based on the study findings, the participants maintained that management of continuing education courses was useful and beneficial, and there was a statistically significant difference between the main variables and the total score (ρ<0.001). The Eta square showed that literacy (ɳ2=0.224, R2=0.462) and gender (ɳ2=0.205, R2=0.345) had less efficiency, and occupation (ɳ2=.581, R2=.219) significantly affected continuous education programs (ρ<0.01). Conclusion: It is suggested that cognitive dimension and occupation should be considered in implementing continuous education programs. Additionally, educational content should be updated